Underground Low Flux Neutron Background Measurements in LSM Using a Large Volume (1m3) Spherical Proportional Counter - Savvidis, I. (HNPS Advances in Nuclear Physics, 2019)
A large volume (1m3) spherical proportional counter has been developed at CEA/Saclay, for low flux neutron measurements. The high voltage is applied to a small sphere 15mm in diameter, located in the center of the counter and the wall of the counter is grounded. Neutrons can be measured successfully, with high sensitivity, using 3He gas in the detector. The proton and tritium energy deposition in the drift gaseous volume, from the reaction 3He(n,p)3H, can provide the neutron spectra from thermal neutrons up to several MeV. The detector has been installed in the underground laboratory in Modane (LSM) to measure the neutron background. The sphere has been has been filled with gas mixture of Ar + 2% CH4 +3gr He-3, at 275 mbar. The thermal neutron peak is well separated from the cosmic ray and gamma background, permitting of neutron flux calculation. Other potential applications requiring large volume of about 10 m in radius are described in detail in reference